2016
DOI: 10.1038/srep31116
|View full text |Cite
|
Sign up to set email alerts
|

Aroma characterization based on aromatic series analysis in table grapes

Abstract: Aroma is an important part of quality in table grape, but the key aroma compounds and the aroma series of table grapes remains unknown. In this paper, we identified 67 aroma compounds in 20 table grape cultivars; 20 in pulp and 23 in skin were active compounds. C6 compounds were the basic background volatiles, but the aroma contents of pulp juice and skin depended mainly on the levels of esters and terpenes, respectively. Most obviously, ‘Kyoho’ grapevine series showed high contents of esters in pulp, while Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
119
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(132 citation statements)
references
References 71 publications
(113 reference statements)
10
119
2
1
Order By: Relevance
“…Terpenes, synthesized from glucose by the isoprenoid pathway, provide a significant floral and fruity aroma to berries (Wu et al, ). Many studies have reported that terpenes and norisoprenoids belong to the grape‐derived compounds and could be used to distinguish the sensory differences in the aromas of grapes (Ferreira et al, ; Noguerol‐Pato et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Terpenes, synthesized from glucose by the isoprenoid pathway, provide a significant floral and fruity aroma to berries (Wu et al, ). Many studies have reported that terpenes and norisoprenoids belong to the grape‐derived compounds and could be used to distinguish the sensory differences in the aromas of grapes (Ferreira et al, ; Noguerol‐Pato et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Active odorants are the direct components of the aromatic series. The specific intensity and tendency of active odorants could be gained through combining subtotal OAVs and odor descriptors (Wu et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations